Biosynthesis of the tunicamycin antibiotics proceeds via unique exo-glycal intermediates. - Wyszynski, F; Lee, S; Yabe, T; Wang, H; Gomez-Escribano, J; Bibb, M; Lee, S; Davies, G; Davis, B (2012)
The tunicamycins are archetypal nucleoside antibiotics targeting bacterial peptidoglycan biosynthesis and eukaryotic protein N-glycosylation. Understanding the biosynthesis of their unusual carbon framework may lead to variants with improved selectivity. Here, we demonstrate in vitro recapitulation of key sugar-manipulating enzymes from this pathway. TunA is found to exhibit unusual regioselectivity in the reduction of a key α,β-unsaturated ketone. The product of this reaction is shown to be the preferred substrate for TunF--an epimerase that converts the glucose derivative to a galactose. In Streptomyces strains in which another gene (tunB) is deleted, the biosynthesis is shown to stall at this exo-glycal product. These investigations confirm the combined TunA/F activity and delineate the ordering of events in the metabolic pathway. This is the first time these surprising exo-glycal intermediates have been seen in biology. They suggest that construction of the aminodialdose core of tunicamycin exploits their enol ether motif in a mode of C-C bond formation not previously observed in nature, to create an 11-carbon chain.